2021
DOI: 10.24198/jkp.v9i3.1669
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Fatique and Stress among Female in Caring for the Elderly at Hospitals

Abstract: Introduction. Studies showed that the caregiving process has an impact on physical and psychological health, such as stress and fatigue.  This research aims to analyze the correlation between fatigue and stress in female caregivers caring for the hospitalized elderly in Medan, Indonesia. Method. This is a correlational study with a cross-sectional approach.  Data collection was conducted from March to October 2020 and 42 caregivers participated.  The data analysis was performed to analyze for frequency distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A research by Zhan et al (2020) showed that there was a significant relationship between stress and nurse fatigue during the pandemic as stated by Huang et al (2019), and Zhan et al (2020). This indicated the role of fatigue in increasing the stress experienced by nurses during the pandemic, as well as to other population in the hospital such as the family caregivers (Tumanggor et al, 2021). Therefore, the more tired a nurse is with the high burden of treating COVID-19 patients, the higher the stress conditions experienced, specifically with the supporting variables such as gender, duration of work, young age, and marital status.…”
Section: Resultsmentioning
confidence: 84%
“…A research by Zhan et al (2020) showed that there was a significant relationship between stress and nurse fatigue during the pandemic as stated by Huang et al (2019), and Zhan et al (2020). This indicated the role of fatigue in increasing the stress experienced by nurses during the pandemic, as well as to other population in the hospital such as the family caregivers (Tumanggor et al, 2021). Therefore, the more tired a nurse is with the high burden of treating COVID-19 patients, the higher the stress conditions experienced, specifically with the supporting variables such as gender, duration of work, young age, and marital status.…”
Section: Resultsmentioning
confidence: 84%
“…Sample's Characteristics However, the research related to the different variables, such as sleep quality and anxiety(Tumanggor & Siregar, 2021) showed a significant relationship compared to sample's characteristics. In addition, research also showed that age associated with some psychological symptoms such as fear(Tumanggor, Imaroh, et al, 2021), and stress(Tumanggor, Kasfi, et al, 2021). So, age is affecting some factors compared to specific cases.…”
mentioning
confidence: 97%
“…However, women are the most affected gender related to COVID-19 impact with social and financial issue(Gausman & Langer, 2020). In terms of psychological effect of COVID-19, female also dominate the result of many studies, such as fear(Tumanggor, Imaroh, et al, 2021), stress(Tumanggor, Kasfi, et al, 2021), caregiving burden(Nuraini et al, 2020) and many more. It is shown that female in some cases affect more research variables compared to men.…”
mentioning
confidence: 99%